Optical coherence tomography of Peripheral retinal lesions in enucleated human eye specimens with histologic correlation II - Ghazi, Nicola G. (2006)
Purpose: To report optical coherence tomography (OCT)-histologic correlations of two peripheral retinal lesions (PRLs) and to emphasize the feasibility of OCT imaging in fixed tissue specimens. Methods: We studied seven formalin-fixed human eyes two of which contained two common peripheral retinal lesions. OCT scans were performed through these lesions and the vitreous base area, and the images were correlated with corresponding histologic sections. Results: Two PRLs including a retinal break and pars plana cysts in addition to the pars plicata and anterior vitreous were successfully imaged. Their optical characteristics correlated well with histology. OCT findings that may help differentiate the hyaloid face and vitreous skirt were also observed. Conclusions: The correlation between OCT images and corresponding histologic sections demonstrates the feasibility of OCT imaging in fixed tissue specimens. Optical characteristics of the vitreous noted in this study may be helpful in understanding disease processes involving the vitreomacular interface.